Studies on Deltamethrin Treated Mosquito Net - A. Tyagi; T. Sharma; M. Singh; K. Fatma; V. S. Rawat; M. Aggarwal; R. K. Khandal (E-Journal of Chemistry)
The focus of the present studies is to characterize mosquito net for its material of construction and qualitative as well as quantitative determination of the mosquito repellent chemical deltamethrin present in it. Further, the assessment of the mode of incorporation of the deltamethrin in the fabric of the mosquito net was done, i.e. whether the deltamethrin was present as a coating on the surface of the mosquito net or it was incorporated in the bulk of the material of construction of the mosquito net. The chromatographic technique has been used for quantitative estimation of deltamethrin extracted by two different solvents from the net. It has been found that the determination of deltamethrin in mosquito nets can vary with the method of extraction used. While extraction with acetone is good enough for estimating the chemical adsorbed on the surface, extraction with xylene provides complete information about the chemical present even in the bulk of the material.